Social Perceptions of Health in Urban and Rural Indonesia - Sashi Kirana H; Ismi; Dewi Yulianti; M Ridwan Said Ahmad; Aila Wilkerson (Jurnal Pendidikan Sosial Indonesia, 2026)
Differences in social, cultural, and service contexts between urban and rural areas in Indonesia shape variations in how health is socially perceived. This article aims to examine how social perceptions of health are constructed in urban and rural communities and to identify the factors influencing these differences. A qualitative approach employing a structured narrative literature review was applied to twenty scholarly articles published over the past decade, which were analyzed through thematic synthesis. The main findings indicate that urban communities tend to conceptualize health within a rational and biomedical, individual-oriented framework, whereas rural communities interpret health in a more communal and context-sensitive manner, influenced by cultural values, social relations, and local authority. Distinctions are also observed in access to health information, perceptions of disease risk, patterns of preventive behavior, and the strength of social norms. This study concludes that health perception is a socially constructed phenomenon shaped by the interaction of structural conditions, cultural orientations, and social capital. The findings imply that health promotion and intervention strategies should be context-sensitive and tailored to the social characteristics of each setting to achieve sustainable outcomes. Perbedaan konteks sosial, budaya, dan ketersediaan layanan antara wilayah perkotaan dan pedesaan di Indonesia membentuk variasi dalam cara masyarakat memaknai kesehatan. Artikel ini bertujuan untuk menganalisis secara komprehensif konstruksi persepsi sosial kesehatan pada masyarakat perkotaan dan pedesaan serta faktor-faktor yang memengaruhinya. Penelitian menggunakan pendekatan kualitatif dengan desain tinjauan literatur naratif-terstruktur terhadap dua puluh artikel ilmiah yang dipublikasikan dalam sepuluh tahun terakhir dan dianalisis melalui sintesis tematik. Temuan utama menunjukkan bahwa masyarakat perkotaan cenderung memahami kesehatan dalam kerangka rasional-medis dan berorientasi individual, sedangkan masyarakat pedesaan memaknainya secara lebih komunal, kontekstual, dan dipengaruhi oleh nilai budaya, relasi sosial, serta otoritas lokal. Perbedaan juga tampak pada akses informasi, persepsi risiko penyakit, pola perilaku pencegahan, serta kekuatan norma sosial. Kajian ini menyimpulkan bahwa persepsi kesehatan merupakan konstruksi sosial yang dibentuk oleh interaksi antara struktur, budaya, dan modal sosial. Implikasinya, strategi promosi dan intervensi kesehatan perlu dirancang secara kontekstual dengan mempertimbangkan karakteristik sosial wilayah agar lebih efektif dan berkelanjutan.